PENGARUH CUSTOMER EXPERIENCE DAN KEPUASAN TERHADAP LOYALITAS PENGUNJUNG DI WONDERLAND ADVENTURE WATERPARK KARAWANG - Rama Rosadi (LPPM UNIVERSITAS BINA INSAN, 2021)
This study aims to test and analyze the influence of customer experience and satisfaction on visitor loyalty at Wonderland Adventure Waterpark Karawang. This research was conducted using quantitative methods with descriptive and verification analysis, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. The sample in this study amounted to 270 using the Non Probability Sampling technique with the incidental sample method. Based on the analysis that has been done, this research proves that the Customer Experience in Wonderland is good, Satisfaction at Wonderland is good enough and Visitor Loyalty is good. The correlation coefficient between the Customer Experience variable and satisfaction has a strong, positive and significant correlation level. The influence of the Customer Experience variable coefficient gives a greater contribution to visitor loyalty than satisfaction. The simultaneous influence of Customer Experience and Satisfaction on Visitor Loyalty is 70.1%, while the remaining 29.9% is the contribution of other variables not examined.